Using the heme peroxidase APEX2 to probe intracellular H2O2 flux and diffusion - Eid, Mohammad; Barayeu, Uladzimir; Sulková, Kateřina; Aranda-Vallejo, Carla; Dick, Tobias P. (Nature Communications, 2024)
Currently available genetically encoded H2O2 probes report on the thiol redox state of the probe, which means that they reflect the balance between probe thiol oxidation and reduction. Here we introduce the use of the engineered heme peroxidase APEX2 as a thiol-independent chemogenetic H2O2 probe that directly and irreversibly converts H2O2 molecules into either fluorescent or luminescent signals. We demonstrate sensitivity, specificity, and the ability to quantitate endogenous H2O2 turnover. We show how the probe can be used to detect changes in endogenous H2O2 generation and to assess the roles and relative contributions of endogenous H2O2 scavengers. Furthermore, APEX2 can be used to study H2O2 diffusion inside the cytosol. Finally, APEX2 reveals the impact of commonly used alkylating agents and cell lysis protocols on cellular H2O2 generation.